Curcumin and Thymoquinone Combination Attenuates Breast Cancer Cell Lines' Progression. (May 2022) - Saddiq, Amna A.; El-Far, Ali H.; Mohamed, Shymaa A.; Almaghrabi, Omar A.; Mousa, Shaker A.
Breast cancer is the most harmful malignancy in women worldwide. Therefore, in the current study, we investigated the combinatory effect of natural bioactive compounds, including curcumin (Cur) and thymoquinone (TQ), on MCF7 and MDA-MB-231 breast cancer cell lines' progression. We investigated the Fa values and combination index of Cur and TQ in this context. Moreover, cytotoxicity percentages, annexin-V, proliferation, colony formation, and migration assays were used along with cell cycle analysis. In addition, caspase-3, phosphatidylinositol 3-kinase (PI3K), and protein kinase B (AKT) protein levels were determined by ELISA assessment. The results showed that Cur, TQ, and Cur + TQ induced apoptosis with cell cycle arrest and decreased cell proliferation, colony formation, and migration activities. Cur + TQ combination significantly increased caspase-3 and decreased PI3K and AKT protein levels. These results suggest the promising anticancer benefit of the Cur and TQ combination against breast cancer.